2016
DOI: 10.1007/s10984-016-9220-y
|View full text |Cite
|
Sign up to set email alerts
|

A cross-national mixed-method study of reality pedagogy

Abstract: This mixed-methods cross-national study investigated the effectiveness of reality pedagogy (an approach in which teachers become part of students' activities, practices and rituals) in terms of changes in student perceptions of their learning environment and attitudes towards science. A questionnaire was administered to 142 students in grades 8-10 in the Bronx, New York City and Dresden, Germany. The questionnaire combines learning environment scales from the Constructivist Learning Environment Survey (CLES) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Within learning environment research, there is a long and rich tradition of using classroom environment criteria as measures of the effectiveness of myriad educational innovations or programs. For example, learning environment characteristics have been used to evaluate outcomes-focused education (Aldridge & Fraser, 2008 ), mixed-mode delivery (Koh & Fraser, 2014 ), using games to teach mathematics at the university level (Afari et al, 2013 ), the professional development of inservice teachers (Nix et al, 2005 ), anthropometry activities in science (Lightburn & Fraser, 2007 ), computer-assisted learning (Teh & Fraser, 1995 ), innovative methods for teaching mathematics (Spinner & Fraser, 2005 ), reality pedagogy (Sirrakos & Fraser, 2017 ), outdoor learning environments (Zaragoza & Fraser, 2017 ), middle-school science laboratory activities (Wolf & Fraser, 2008 ) and alternative science topic arrangements (Long et al, 2020 ). The study reported in this article adds to the field of learning environments because it is probably the first to use learning environment criteria in investigating the impact of the sudden disruption to instruction caused by the COVID-19 pandemic.…”
Section: Theoretical Perspective: Field Of Learning Environmentsmentioning
confidence: 99%
“…Within learning environment research, there is a long and rich tradition of using classroom environment criteria as measures of the effectiveness of myriad educational innovations or programs. For example, learning environment characteristics have been used to evaluate outcomes-focused education (Aldridge & Fraser, 2008 ), mixed-mode delivery (Koh & Fraser, 2014 ), using games to teach mathematics at the university level (Afari et al, 2013 ), the professional development of inservice teachers (Nix et al, 2005 ), anthropometry activities in science (Lightburn & Fraser, 2007 ), computer-assisted learning (Teh & Fraser, 1995 ), innovative methods for teaching mathematics (Spinner & Fraser, 2005 ), reality pedagogy (Sirrakos & Fraser, 2017 ), outdoor learning environments (Zaragoza & Fraser, 2017 ), middle-school science laboratory activities (Wolf & Fraser, 2008 ) and alternative science topic arrangements (Long et al, 2020 ). The study reported in this article adds to the field of learning environments because it is probably the first to use learning environment criteria in investigating the impact of the sudden disruption to instruction caused by the COVID-19 pandemic.…”
Section: Theoretical Perspective: Field Of Learning Environmentsmentioning
confidence: 99%
“…Several studies have shown that when the principles of reality pedagogy are used in teaching and learning contexts, learners are motivated and subsequently improve their academic performance. For instance, a cross-national study by Sirrakos and Fraser (2017) in the Bronx, New York, Dresden, and Germany found that reality pedagogy is a practical approach to teaching and learning science. Similarly, there is multiple established empirical evidence claiming the effectiveness of all key principle characteristics of reality pedagogy in teaching and learning science (Borges, 2016;Singh et al, 2002;Sirrakos & Fraser, 2017a).…”
Section: Academic Performance and Motivation Using Reality Pedagogymentioning
confidence: 99%
“…Physics revealed that the new and the traditional physics curriculum could be distinguished in terms of students' classroom environment perceptions (using the Learning Environment Inventory) when a range of student outcome measures showed little differentiation (Welch & Walberg, 1972). Subsequently, learning environment dimensions have continued to be used as criteria of effectiveness in evaluating teacher professional development (Nix, Fraser & Ledbetter, 2005), field study centres (Zaragoza & Fraser, 2017), National Board certification of teachers (Helding & Fraser, 2013), inclusion of games in mathematics teaching (Afari, Aldridge, Fraser & Khine, 2013), computer-assisted learning (Teh & Fraser, 1995), use of reality pedagogy in science teaching (Sirrakos & Fraser, 2017), the implementation of student response systems (Cohn & Fraser, 2016) and 'flipped' classrooms (Strayer, 2012).…”
Section: Determinants Of Learning Environment (Including Evaluation O...mentioning
confidence: 99%